2023
DOI: 10.1007/s10439-023-03322-x
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Analysis of Additive Manufacturing Techniques in the Bioengineering of In Vitro Cardiovascular Models

Hemanth Ponnambalath Mohanadas,
Vivek Nair,
Akbar Abbas Doctor
et al.

Abstract: Additive Manufacturing is noted for ease of product customization and short production run cost-effectiveness. As our global population approaches 8 billion, additive manufacturing has a future in maintaining and improving average human life expectancy for the same reasons that it has advantaged general manufacturing. In recent years, additive manufacturing has been applied to tissue engineering, regenerative medicine, and drug delivery. Additive Manufacturing combined with tissue engineering and biocompatibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…Both aspects are undergoing significant enhancements through the evolution of software. [16][17][18] Although more studies are needed to fully understand the impact, 3D models have shown potential to improve clinical outcomes, doctor-patient communication, pre-operative planning, surgeon confidence, and reduce operation time. [4][5][6][7] In this clinical case, the authors encountered several challenges in performing endovascular treatment due to a narrow and angulated neck and extensive atherosclerotic disease of renal arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both aspects are undergoing significant enhancements through the evolution of software. [16][17][18] Although more studies are needed to fully understand the impact, 3D models have shown potential to improve clinical outcomes, doctor-patient communication, pre-operative planning, surgeon confidence, and reduce operation time. [4][5][6][7] In this clinical case, the authors encountered several challenges in performing endovascular treatment due to a narrow and angulated neck and extensive atherosclerotic disease of renal arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Both aspects are undergoing significant enhancements through the evolution of software. 1618 Although more studies are needed to fully understand the impact, 3D models have shown potential to improve clinical outcomes, doctor-patient communication, pre-operative planning, surgeon confidence, and reduce operation time. 47…”
Section: Discussionmentioning
confidence: 99%